Ignition systems for lean burn gas engines - Pashley, NC (1997)
This thesis describes an experimental investigation into ignition systems, their effects on the combustion process, and how the discharge is affected by the prevailing pressure, temperature and flow. The work is divided into four main areas, a comprehensive literature review, engine testing for ignition system suitability, non-flow rig testing (including erosion) and flow rig testing. The literature review concluded that the most practical ignition system for lean burn gas engines will continue to be based on the spark plug, but in the medium to long term, laser ignition may become viable. The measurement of the HT voltage and current is not straightforward, and appropriate methods have been identified. Capacitive and inductive ignition system types were compared in lean and diluted conditions on a single cylinder research engine of modern design at different engine loads and speeds. It was found that the most beneficial ignition system was an inductive ignition system, although that for some conditions, capacitive systems induced better engine performance with a fraction of the stored energy of the inductive alternative. Non flow tests showed that the early part of the spark discharge is sensitive to pressure and temperature effects, and as a consequence, the latter stages of the discharge are also affected. A correlation has been developed, for use with conventional nickel electrode spark plugs, to predict breakdown voltage as a function of pressure, temperature and gap. Experiments were carried out at elevated pressures in a stream of flowing air with capacitive and inductive ignition systems. Different electrode designs and orientations were also compared. It was shown that when exposed to a flow field, the discharge can be stretched which results in a shortened spark duration; in some cases the electrode can shield the discharge from flow field effects. This work showed that flow through the spark gap is a hindrance to the spark process, especially for longer duration systems. However for flame kernel growth, the literature review identified that flow is beneficial, serving to convect the kernel away from the electrodes, reducing the heat transfer from the flame. Analysis of the glow voltage history in the pressurised flow rig has been used to develop a correlation relating the voltage, current, flow velocity, pressure and time. This correlation was used to analyse the velocity records from the spark plug in a firing engine. The predicted velocities and turbulence intensity were in agreement with independent measurements.